Methodologies for Bridging the Digital Divide amongst Remote and Rural Communities in Peninsular Malaysia - Poline, Bala; Tan, Chong Eng (UNIMAS Publisher, 2018)
The Telecentre Programme for Orang Asli (TPOA) was developed and designed to introduce information and communication technology (ICTs) for bridging the digital divide between urban and rural communities, targeting mainly four Orang Asli communities in Kelantan and Pahang. This report is a window into the implementation model and service design of TPOA at Pos Sinderut, Pos Lenjang, Pos Balar and Pos Gob. Beginning with the inception stage in February 2011, the journey has taken about 7 years to attain its final stage, which is to evaluate, assess and monitor. The experience has involved two different periods of research and development activities, supported by two different grants worth RM1.3 million (Needs Assessment Stage) and RM4.9 million (Telecentre Programme Roll Out Stage), respectively. About 37 researchers with diverse skills from different fields and diverse disciplines took part in the different stages of the initiative; some have moved on for various reasons while some have stayed put until the finishing line. Guided by multi disciplinarian approaches, the initiative has pulled together different agencies (governmental and nongovernmental, academic and non-academic, local and nonlocal) and institutions to collaborate. The initiative is an excellent example of a multi-level collaborative and practical approaches in deploying ICT amongst rural, remote and indigenous communities.